218k views
4 votes
Help plzzz
Select the correct answer.


Help plzzz Select the correct answer. ​-example-1
User Tjleigh
by
4.5k points

1 Answer

1 vote

Answer: C) 3

=========================================================

Step-by-step explanation:

f(x) is the outer function, so the final output -8 corresponds to f(x)

We see that f(-4) = -8 in the first column of the table. I'm starting with the output and working my way backward to get the input. So we started with -8 and worked back to -4.

Then we move to the g(x) function to follow the same pattern: start with the output and move to the input. We start at -4 in the g(x) bubble and move to 3 in the x bubble.

In short, g(3) = -4

So,

f(g(x)) = f(g(3)) = f(-4) = -8

We see that x = 3 leads to f(g(x)) = -8

User TheEsnSiavashi
by
4.4k points